Interactive Multimedia on Learning Achievement of the Digestive System in Elementary School - Fitria, Yanti; Lili Iswari; Risda Amini; Muhammad Kristiawan; Ari Kiswanto (Universitas Pendidikan Ganesha, 2022)
The lack of careful selection of science learning media for fifth grade elementary school encourages this research. The aim of this project is to create a legitimate, useful and efficient interactive multimedia (MI) product for 5th grade science classes in elementary schools. Development research is the methodology used. The ADDIE development model is used in this study. The type of data taken in this study is primary data. The subjects of this study were 21 students and teachers of class V in an elementary school. Instrument validation charts, language instruments, material instruments, practicality sheets, and test question sheets are among the data collection tools. The data analysis technique is adapted to the data collection equipment. The validation sheet was used to perform the validation analysis, which was carried out using a Likert scale. The research findings show positive results in terms of validity, practicality, and effectiveness of the developed interactive multimedia. This study resulted in three findings, namely: (1) MI is valid at an average value of 4.7 with very valid qualifications (2) practical at an average value of 89.03 very practical qualifications and (3) effective in increasing student learning success at grades an average of 94.8 (95% success). The conclusion of this study is that the MI Digestive System is effective in increasing student achievement.